INNOVATION OF KUTA MIMBA MOBILE: ENHANCING EFFICIENCY AND PARTICIPATION IN DIGITAL WASTE BANKS - Surya Dewi Rustariyuni; AAIN Marhaeni; I Nyoman Widya Arta (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
Waste issues constitute a global problem, requiring public awareness of the importance of proper waste management. Waste management initiated at the household level is carried out by the Family Welfare Empowerment community of Banjar Buni Kuta through the Bumiku Resik Waste Bank, followed by manual recording of each transaction for every customer. This process has led to several problems and challenges; therefore, an innovation in digital waste bank management was implemented through collaboration with the Kuta Mimba Savings and Loan Cooperative via the Kuta Mimba Mobile Digital Waste Bank application. This study employs a descriptive method with a qualitative approach. Informants were selected purposively, consisting of three key informants and fifteen secondary informants. Data were collected through observation, interviews, and documentation to obtain information relevant to the research focus. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana. The results indicate benefits experienced by cadres, customers, and the Kuta Mimba Savings and Loan Cooperative through the collaboration in implementing digital waste bank innovation. Cadres benefit from time efficiency, accountability, and transparency for customers. Customers benefit from additional alternative income, the sustainability of a clean environment, and access to various digital services provided by Kuta Mimba Mobile. The Kuta Mimba Savings and Loan Cooperative benefits as a social media platform, a promotional medium for increasing membership, and for product and service development. The implications of this study show that community participation is able to maintain environmental sustainability in line with the Sustainable Development Goals, as well as enhance digital financial literacy within the community.